HIJAB ACCORDING TO THE INTERPRETATION OF QURAISH SHIHAB AND MUSTHAFA AL-MARAGHI - Amin Mukrimun, Amin Mukrimun; Moh. Faisal Aulia; Almurtaqi, Moch Ridwan; Muchlisin, Imam (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
Hijab is a garment that is obligatory by Allah for Muslim women. In the Qur'an there are arguments related to the hijab. Among them is the Qur'an letter an-Nur verse 31. However, in understanding this verse, the mufassir differed on whether the headscarf is an obligation or a recommendation, and whether the face must be covered with a headscarf or not. Then how about the boundaries of women's genitals. The author takes the mufassir figures M. Quraish Shihab and Mustafa al-Maraghi. Because the two figures have different understandings in interpreting the verse about the headscarf, they agree that the headscarf is a Muslim dress that is used to cover a woman's private parts. This paper uses comparative studies and Hans George Gadamer's hermeneutic theory. Gadamer in his theory says that in interpreting, the interpreter is not in a vacuum. The interpreter's pre-understanding which is influenced by social, political, economic and scientific conditions greatly determines the results of interpretation.